The Risk-Taking Channel of Monetary Policy Transmission in the Euro Area - Matthias Neuenkirch; Matthias Nöckel (Center for Economic Studies and ifo Institute (CESifo), 2018)
In this paper, we provide evidence for a risk-taking channel of monetary policy transmission in the euro area that works through the relaxation of lending standards for borrowers. Our dataset covers the period 2003Q1-2016Q2 and includes, in addition to the standard variables for real GDP growth, inflation, and the monetary policy stance, indicators of bank lending standards and bank lending margins. Based on vector autoregressive models with (i) recursive identification and (ii) sign restrictions, we show that banks react aggressively to an expansionary monetary policy shock by lowering their lending standards. The banks' efforts to keep their lending margin stable, however, are not successful as we detect a significant compression. We document these findings for the euro area as a whole and for its individual member states. In particular, banks in the Netherlands, Portugal, Spain, and Ireland lowered their lending standards after expansionary monetary policy shocks. The compression of the lending margin is most pronounced in the five crisis countries (Greece, Ireland, Italy, Portugal, and Spain).
Keywords: E44; E51; E52; E58; G28; 330; European Central Bank; macroprudential policy; monetary policy transmission; risk-taking channel; vector autoregression